Arthroscopic suprascapular neurectomy for the management of severe shoulder pain. - Mohd Nasir, Mohd Nizlan; Skirving, Allan P.; Campbell, Peter T. (Elsevier, 2009)
Hypothesis: Arthroscopic suprascapular neurectomy is an effective option in the management of patients with severe shoulder pain.